2016
DOI: 10.1002/2016gl069624
|View full text |Cite
|
Sign up to set email alerts
|

Waveform inversion of acoustic waves for explosion yield estimation

Abstract: We present a new waveform inversion technique to estimate the energy of near‐surface explosions using atmospheric acoustic waves. Conventional methods often employ air blast models based on a homogeneous atmosphere, where the acoustic wave propagation effects (e.g., refraction and diffraction) are not taken into account, and therefore, their accuracy decreases with increasing source‐receiver distance. In this study, three‐dimensional acoustic simulations are performed with a finite difference method in realist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…The box-and-whisker plot in Figure 4 shows a distribution of SPLs predicted from 20 random realizations of the boundary layer. This distribution can be considered as an empirical probability distribution of sound pressure (Blom et al, 2015;Ostashev & Wilson, 2015) and can be useful to evaluate source inversion uncertainty depending on atmospheric variability (Fee et al, 2017;Kim & Rodgers, 2016;Kim et al, 2015). Although the variance of the prediction uncertainty is related to the characteristic length scale and intensity of the stochastic turbulence, the median predictions are largely impacted by the vertical profile used for atmospheric representation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The box-and-whisker plot in Figure 4 shows a distribution of SPLs predicted from 20 random realizations of the boundary layer. This distribution can be considered as an empirical probability distribution of sound pressure (Blom et al, 2015;Ostashev & Wilson, 2015) and can be useful to evaluate source inversion uncertainty depending on atmospheric variability (Fee et al, 2017;Kim & Rodgers, 2016;Kim et al, 2015). Although the variance of the prediction uncertainty is related to the characteristic length scale and intensity of the stochastic turbulence, the median predictions are largely impacted by the vertical profile used for atmospheric representation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…This observation suggests that the SPLs and their large variances were likely caused by the wind variability (Kim & Rodgers, 2017). The sound pressure reduction model is often important to infer source characteristics such as explosion yield (Kim & Rodgers, 2016) and explosive mass flow (Johnson & Miller, 2014;Kim et al, 2015). Without accounting for the atmospheric path propagation effects, the inferred source parameters may suffer from large errors.…”
Section: Acoustic Overpressure Datamentioning
confidence: 99%
“…A full waveform inversion technique is employed to estimate explosion yields from acoustic signals. Acoustic signals at local distance, here defined as within 15‐km propagation distance (Kim & Rodgers, ), are inverted for acoustic source time functions which represent expanding volume of air at detonation and can be used as a proxy for explosion energy (Kim & Rodgers, ). Details of the acoustic waveform inversion and associated probability representation were described in Kim et al (), Kim, Rodgers, & Wright, (), and Kim and Rodgers ().…”
Section: Acoustic Yield Methodologymentioning
confidence: 99%
“…In this study, we take a time domain approach which provides source time history ( q ( t )) directly without the need of a frequency‐to‐time domain transformation. Kim and Rodgers () showed that the peak mass flow rate corresponds to the reduced acoustic impulse which is a robust source parameter for explosion yield estimation. They related the reduced acoustic impulse I to the yield of explosion based on an air‐blast model: Ipred=Iref0.25emft0.25emW2/3 where W is the yield of explosion, I ref is a reference reduced acoustic impulse for 1‐kg TNT explosion, and f t is a scaling parameter.…”
Section: Acoustic Yield Methodologymentioning
confidence: 99%
See 1 more Smart Citation